Hyophorbe verschaffeltii, Spindle Palm - Melissa H. Friedman; Michael G. Andreu; Heather V. Quintana; Mary McKenzie (EDIS, 2010)
FOR 241, a 2-page fact sheet by Melissa H. Friedman, Michael G. Andreu, Heather V. Quintana, and Mary McKenzie, describes this palm with a spindly stem, which is endemic to the Mascarene Islands east of Madagascar, and which in the U.S. grows in south Florida, southern California, and the Hawaiian Islands – scientific and common names, description, and applications. Includes references. Published by the UF School of Forest Resources and Conservation, May 2010.